2013
DOI: 10.1177/0954407012469498
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the wobble mode stability of a three-wheeled vehicle

Abstract: A wobble instability is one of the major problems of a three-wheeled vehicle commonly used in India, and these instabilities are of great interest to industry and academia. In this paper, we studied this instability using a multi-body dynamic model and with experiments conducted on a prototype three-wheeled vehicle on a test track. The multi-body dynamic model of a three-wheeled vehicle is developed using the commercial software ADAMS/Car. In an initial model, all components including main structures such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…By contrast, the shimmy models of Wang et al, 11 Wei and Jiang, 12 Lu et al, 8 Li and Lin 9 and Wei et al 10 are based on real vehicle-related multi-DoF systems with emphases either on the influence of different parameters of the model with independent suspensions or on the analysis of the model with dependent suspension. Karanam and Ghosal 13 established a multi-body dynamic model of a three-wheeled vehicle, the simulation results of which showed that the flexibility of the steering column can cause system instability. The shimmy of aircraft nose landing gear has also received a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the shimmy models of Wang et al, 11 Wei and Jiang, 12 Lu et al, 8 Li and Lin 9 and Wei et al 10 are based on real vehicle-related multi-DoF systems with emphases either on the influence of different parameters of the model with independent suspensions or on the analysis of the model with dependent suspension. Karanam and Ghosal 13 established a multi-body dynamic model of a three-wheeled vehicle, the simulation results of which showed that the flexibility of the steering column can cause system instability. The shimmy of aircraft nose landing gear has also received a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…The results are verified by simulation, and should eventually be validated against physical tests. Additional analysis such as those for 'wobble' (seen on three-wheeled rickshaws) [14] are neglected here.…”
Section: Modelling Approachmentioning
confidence: 99%
“…15 In addition, they are already an important part of transportation vehicles in some Asian countries. 16 3W vehicles can be designed with two different configurations. 17,18 The first configuration, called the delta configuration, has one wheel in the front and two wheels in the rear.…”
Section: Introductionmentioning
confidence: 99%